Improved quantitative analysis of primary bone marrow megakaryocytes utilizing imaging flow cytometry. Issue 4 (16th January 2014) - Niswander, Lisa M.; McGrath, Kathleen E.; Kennedy, John C.; Palis, James
Abstract Life‐threatening thrombocytopenia can develop following bone marrow injury due to decreased platelet production from megakaryocytes (MKs). However, the study of primary MKs has been complicated by their low frequency in the bone marrow and by technical challenges presented by their unique maturation properties. More accurate and efficient methods for the analysis of in vivo MKs are needed to enhance our understanding of megakaryopoiesis and ultimately develop new therapeutic strategies for thrombocytopenia. Imaging flow cytometry (IFC) combines the morphometric capabilities of microscopy with the high‐throughput analyses of flow cytometry (FC). Here, we investigate the application of IFC on the ImageStreamX platform to the analysis of primary MKs isolated from murine bone marrow. Our data highlight and address technical challenges for conventional FC posed by the wide range of cellular size within the MK lineage as well as the shared surface phenotype with abundant platelet progeny. We further demonstrate that IFC can be used to reproducibly and efficiently quantify the frequency of primary murine MKs in the marrow, both at steady‐state and in the setting of radiation‐induced bone marrow injury, as well as assess their ploidy distribution. The ability to accurately analyze the full spectrum of maturing MKs in the bone marrow now allows for many possible applications of IFC to enhance our understanding of megakaryopoiesis and platelet production. © 2014 International Society for Advancement of Cytometry